A Novel Case of Functional Gastric Neuroendocrine Carcinoma Occurred after Endoscopic Submucosal Dissection. (6th November 2013) - Shibata, Yoshiaki; Ito, Yuji; Fujita, Hiroko; Okada, Yume; Nagai, Toshihiko; Sano, Hirohito; Ito, Kumiko
Abstract : In Japan, endoscopic submucosal dissection (ESD) is becoming a standard treatment for intramucosal differentiated gastric cancer. Although ESD is associated with a high cure rate for patients with early gastric cancer, tumors may recur, albeit rarely. We performed ESD on an 80-year-old man with a small depressed type of gastric cancer of the posterior wall of the cardia, found to be locally invasive on histology. Thirty months later, local recurrence and multiple liver metastases were detected, accompanied by frequent severe hypoglycemia. Despite chemotherapy, the patient died 6 months after relapse. On autopsy, the recurrent gastric lesion and liver metastases were examined immunohistochemically. Several characteristic tumor cells were positive for chromogranin A, cluster of differentiation (CD) 56, Ki-67, and insulin-like growth factor (IGF)-II. Western blot analysis of the patient's serum obtained during a hypoglycemic attack showed the high molecular weight form of IGF-II or "big" IGF-II. The patient was diagnosed with non-islet cell tumor hypoglycemia (NICTH), with "big" IGF-II being produced by the gastric neuroendocrine carcinoma. This is the novel case of a functional gastric neuroendocrine carcinoma that occurred after ESD and induced a hypoglycemic attack associated with NICTH.